Breast milk macronutrients in fasting vs. non‐fasting lactating women - AKTAÇ, ŞULE; KUNDAKÇI, SİMAY (My University, 2023)
Background:Breastfeeding is one of the most important factors ensuring the healthy growth and development of babies. While the literature has shown regarding the impact of maternal nutrition status on breast milk, those investigating the impact of religious fasting on breast milk composition remain scarce.Objectives:We aimed to compare breast milk macronutrients of the fasting and non‐fasting lactating women during Ramadan.Methods:We enrolled 21 fasting and 27 non‐fasting women, who exclusively fed their infants with breast milk during Ramadan month in 2021. We collected breast milk samples and compared levels of energy, carbohydrate, protein, and lipids. In addition, we compared the subject groups by their dietary intake of macro and micronutrients.Results:Fasting and non‐fasting women were similar by their education status, age and BMİ before pregnancy, at birth, and the time of breast milk sampling. The study groups did also not differ by infant\"s age, sex, birth weight, height, gestational week, and actual weight, height (p > 0.05). Energy, carbohydrate, protein, and lipid composition of the breast milk were similar in the groups. We detected no statistically significant difference in daily intake of nutrition between fasting and non‐fasting women. The mean daily intake of lipids was significantly higher in fasting women compared to that in non‐fasting women (p < 0.05). We also found significantly higher mean daily intake of sodium, chloride and omega‐3 fatty acids in the fasting group than that in non‐fasting group.Conclusion:Our study suggests no substantial impact of the religious fasting on energy and macronutrient composition of the breast milk.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)